Pengaruh Promosi Di Media Sosial Tiktok Dan Pemanfaatan Customer Relationship Management (CRM) Terhadap Penjualan Skincare Kahf Di Cikarang Barat - Adji Nugroho (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to determine the effect of service quality on customer satisfaction at the Samsat Corner Cikarang outlet during the period of March–July 2024. The research uses a quantitative method with a purposive sampling technique, involving 82 respondents from a population of 200 people. Data collection was conducted through questionnaires and analyzed using various statistical tests, including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, and hypothesis testing (t-test and f-test). The results indicate that service quality has a significant effect on customer satisfaction, with an R Square value of 50.1%, meaning that 49.9% is influenced by other factors. The t-test results show that the t-value (5.183) is greater than the t-table value (1.66365) with a significance level of 0.000 < 0.05. Additionally, the f-test results indicate that the f-value (25.657) is greater than the f-table value (3.96), further confirming that service quality significantly impacts customer satisfaction.The conclusion of this study is that improving the quality of vehicle tax payment services at the Samsat Corner Cikarang outlet can enhance customer satisfaction.